2020
DOI: 10.1016/j.medj.2020.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lopinavir/Ritonavir or Arbidol in Adult Patients with Mild/Moderate COVID-19: An Exploratory Randomized Controlled Trial

Abstract: Several drugs are being tested against the novel coronavirus SARS-CoV-2, the pathogen responsible for the COVID-19 pandemic. Li et al. show that the drugs lopinavir/ritonavir and arbidol, which are currently used against HIV-1 and influenza, respectively, show little benefit over supportive care in patients with mild and moderate COVID-19.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
328
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(339 citation statements)
references
References 15 publications
(16 reference statements)
5
328
0
6
Order By: Relevance
“…Two trials compared remdesivir versus placebo [ 32 , 44 ]. Two trials compared lopinavir–ritonavir added to standard care versus standard care alone [ 33 , 41 ]. Eight trials compared hydroxychloroquine added to standard care versus standard care alone [ 35 , 36 , 43 , 49 , 55 , 56 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two trials compared remdesivir versus placebo [ 32 , 44 ]. Two trials compared lopinavir–ritonavir added to standard care versus standard care alone [ 33 , 41 ]. Eight trials compared hydroxychloroquine added to standard care versus standard care alone [ 35 , 36 , 43 , 49 , 55 , 56 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…We included 12 RCTs, 3 non-RCTs and 20 observational (including retrospective/prospective cohort, case-control) studies. Eighteen studies were from China, 10,11,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] six from USA, [47][48][49][50][51][52] five from Italy, [53][54][55][56][57] two from France 6,58 and one each from Brazil, 59 Hong Kong, 60 Spain 61 and Greece. 62 There was no significant difference in the mean age and sex distribution between any of the treatment and comparator groups included in our meta-analysis.…”
Section: Results From Clinical Studiesmentioning
confidence: 99%
“…Four studies [35][36][37][38] consisting of 397 nCOV-2019 cases were included in the meta-analysis and were divided into two groups: 227 subjects to lopinavir-ritonavir group and 170 subjects control group. There was no significant association between the two groups in terms of total adverse events (RR 1.73; 95%CI 0.57 to 5.26) and overall clinical recovery (RR 1.08; 95%CI 0.94 to 1.24).…”
Section: Lopinavir-ritonavir Vs Control Groupsmentioning
confidence: 99%
“…The screening process was shown in figure 1 and 3860 studies were identified according to the research strategy initially. In total, 22 studies containing 12795 patients were adopted in our study and all of them were published in English 10,12,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] . Among trails included, half of them were RCTs, and the other were Non-RCTs.…”
Section: Literature Researchmentioning
confidence: 99%